Elite Women and the Agricultural Landscape, 1700-1830 (Taylor & Francis, 2018)
Social and economic histories of the long eighteenth century have largely ignored women as a class of landowners and improvers. 1700 to 1830 was a period in which the landscape of large swathes of the English Midlands was reshaped - both materially and imaginatively - by parliamentary enclosure and a bundle of other new practices. Outside the Midlands too, local landscapes were remodelled in line with the improving ideals of the era. Yet while we know a great deal about the men who pushed forward schemes for enclosure and sponsored agricultural improvement, far less is known about the role played by female landowners and farmers and their contributions to landscape change. Drawing on examples from across Georgian England, Elite Women and the Agricultural Landscape, 1700-1830 offers a detailed study of elite women's relationships with landed property, specifically as they were mediated through the lens of their estate management and improvement. This highly original book provides an explicitly feminist historical geography of the eighteenth-century English rural landscape. It addresses important questions about propertied women's role in English rural communities and in Georgian society more generally, whilst contributing to wider cultural debates about women's place in the environmental, social and economic history of Britain. It will be of interest to those working in Historical and Cultural Geography, Social, Economic and Cultural History, Women's Studies, Gender Studies and Landscape Studies.
English
Keywords: c 1500 onwards to present day; History and Archaeology; History; Social and cultural history; eighteenth century; estates; History; landscape; property; women